THE POLITICAL CONCEPT OF THE “MANAGERIAL REVOLUTION” IN THE WORKS OF JAMES BURNHAM - Milić, Dimitrije (Political Review, 2025)
James Burnham, a 20th-century American conservative thinker, is best known for his concept of the “managerial revolution,” as presented in his 1941 work of the same name. Burnham identifies a new managerial elite, emerging from the owners’ need for experts capable of managing complex, international processes, as the successors of previous capitalist and socialist structures. In line with their growing social role, Burnham examines the influence of the managerial elite in both the public and private sectors, analyzing the consequences of this transformation for the democratic system. Although Burnham’s work did not find a place in the ideological mainstream, his thought has had a particular influence in contemporary conservative and populist circles. This paper aims to provide a critical reflection on the concept of managerialism and its impact on the transformation of social elites, power relations, and the nature of democracy.